Assessment of structural integrity via wavelet based time-frequency analysis of vibration signals. (1st June 2007) - Basu, Biswajit
An approach for assessment of structural integrity via wavelet analysis based Structural Health Monitoring (SHM) is presented here. The success of the approach relies on the information available in the form of local (in time) frequency content of the vibration signals. Results from three typical case studies are reviewed and outlined in this paper. The first one is a study based on hysteretic structures. The second example is for a linear time varying Multi-Degree-Of-Freedom (MDOF) system with time varying natural frequencies and mode shapes. The third case considered is an experimental study on the seismic response of concentrically braced frames.